2021
DOI: 10.1080/15384101.2021.1930356
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of miR-93-5p and its effect on the radiosensitivity of breast cancer

Abstract: Accumulating evidence suggests that intrinsic resistance to radiotherapy reduces the survival of patients with cancer. The present study investigated whether miR-93-5p affects proliferation, migration, apoptosis, and radiosensitivity of breast cancer (BC) cells. MDA-MB-468, MCF-7, and MDA-MB-231 BC cells were incubated with hsa-miR-93-5p mimics, hsa-miR-93-5p inhibitor, and negative control RNA with or without exposure to ionizing radiation to determine cell proliferation, migration, and apoptosis using the Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…miRNA regulates most of the genes and employed in various cellular processes such as cell proliferation, differentiation, metabolism, and apoptosis [ 13 ]. Currently, miRNA has been used as biomarker for disease diagnosis in many clinical fields, such as cardiovascular and cerebrovascular diseases, autoimmune diseases, and tumors [ 14 , 15 ]. Studies have shown that miR-223 is highly expressed in peripheral blood of SP patients and can be used as an early diagnostic marker for severe pneumonia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA regulates most of the genes and employed in various cellular processes such as cell proliferation, differentiation, metabolism, and apoptosis [ 13 ]. Currently, miRNA has been used as biomarker for disease diagnosis in many clinical fields, such as cardiovascular and cerebrovascular diseases, autoimmune diseases, and tumors [ 14 , 15 ]. Studies have shown that miR-223 is highly expressed in peripheral blood of SP patients and can be used as an early diagnostic marker for severe pneumonia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…After intersecting with 289 DEmiRNAs, 25 miRNAs were obtained. Among them, 7 miRNAs (miR-671-5p, miR-940, miR-124-3p, miR-944, miR-93-5p, miR-512-3p and miR-142-5p) have been reported in breast cancer ( Flores-Pérez et al, 2016 ; Tan et al, 2016 ; Wang et al, 2016 ; Zhang et al, 2020a ; Elango et al, 2020 ; Mohamadzade et al, 2021 ; Pan et al, 2021 ). For instance, overexpression of miR-671-5p suppressed FOXM1 expression, thereby reducing breast cancer cells growth and invasion ( Tan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124-3p could inhibit the proliferation of MCF-7 and MDA-MB-231 cells by suppressing CBL expression ( Wang et al, 2016 ). Pan et al (2021) showed that an increase in miR-93-5p could radiosensitize breast cancer cells by increasing apoptosis. Furthermore, we obtained 1,148 mRNAs targeted by these 25 miRNAs based on three online databases.…”
Section: Discussionmentioning
confidence: 99%
“…miR-142-5p overexpression may increase breast cancer proliferation, invasion, and migration when SORBS1 is targeted [ 37 ]. Increased apoptosis and decreased recurrence rate are associated with increased radio-sensitivity of breast cancer cells when miR-93-5p is overexpressed, implying the role of miR-93-5p may act as a potential therapeutic target for breast cancer [ 38 ]. miR-17-5p may have an important effect on pathogenesis of triple-negative breast cancer, and its increased expression is associated with prognosis, implying the role of miR-17-5p as the therapeutic target for triple-negative breast cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%